2012
DOI: 10.1007/s00216-012-5780-6
|View full text |Cite
|
Sign up to set email alerts
|

Normalisation of data from allergens proficiency tests

Abstract: The problem of allergen analysis using ELISA kits from different commercial products giving significantly different results is widely acknowledged. The effect on proficiency testing results is that different assigned values have to be generated for the different kits used. Some experimental Food Analysis Performance Assessment Scheme (FAPAS) proficiency tests aimed to establish whether the use of a standardised calibrant could be used to normalise the complete data set without recourse to differentiation. Thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…Judging by the available literature (Allred and Ritter 2010;Bruins Slot et al 2015a;Bugyi et al 2013;Rallabhandi et al 2015;Sharma et al 2015), these results were not unexpected, mostly because of the different characteristics of the ELISA test kits (Table 1) that cause systematic deviations (Sykes et al 2012). As the first step, the gluten extraction procedure has an important influence on the analytical results.…”
Section: Discussionmentioning
confidence: 91%
“…Judging by the available literature (Allred and Ritter 2010;Bruins Slot et al 2015a;Bugyi et al 2013;Rallabhandi et al 2015;Sharma et al 2015), these results were not unexpected, mostly because of the different characteristics of the ELISA test kits (Table 1) that cause systematic deviations (Sykes et al 2012). As the first step, the gluten extraction procedure has an important influence on the analytical results.…”
Section: Discussionmentioning
confidence: 91%
“…It was shown that a standardised calibrant (e.g. a matrix-matched standard) can be successfully used to normalise the data set from different allergen ELISA kits (Sykes et al, 2012). More recently, a dessert matrix incurred with pasteurised egg white or skimmed milk powder was produced and evaluated in a multilaboratory trial as a promising quality control material for food allergen analysis (Johnson et al, 2014).…”
Section: Enzyme-linked Immunosorbent Assaymentioning
confidence: 99%
“…43 In proficiency testing multimodal datasets for allergen ELISAs are common and different assigned values have to be generated for the different kits used. 44 Recent work on precautionary labelling on pre-packed processed food and concentrations of certain cross contaminant allergens in foods suffered from unexpected cross reactivity in the commercial ELISA. False positive results were identified arising from an Association of Analytical Communities (AOAC) approved peanut assay owing to cross reactivity to soya.…”
Section: Allergen Analysismentioning
confidence: 99%
“…Sykes et al 44 showed that inclusion of a 'reference spiked sample' in a Proficiency Test, PT, round where the raw data were non-normal and multi-modal, tended to yield ratio data that were normal and symmetrically distributed. These authors, and (non-exhaustively) many others [51][52][53][54] call for the development of internationally recognised sets of allergen reference materials to improve the reliability of allergen analysis.…”
Section: Reference Materialsmentioning
confidence: 99%